(untitled) (Journal of Nepal Geological Society, 2011)
The wedge stability and stress analyses are important in tunnel stability assessment. The identification of the wedge stability and stress condition for the headrace tunnel suggests the required tunnel support in Lower Balephi Hydroelectric Project in Sindhupalchock District, central Nepal. The planned tunnel of the project is 4.5 min diameter and 4.2 km in length. The main litholog ies of the area along the tunnel axis are phyllite and phyllitic quartzite of the Kunchha Formation, Nawakot Complex. Wedge stability analysis in the headrace tunnel showed that the structural wedge would form due to excavation and can be stabilized with the help of rock bolting and shotcreting. Rock squeezing is predicted to occur in high tunnel depth in phyllite and it may be stabilized with the installation of roc k support consisting steel rib.